Penerapan Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Dewi, Desy Triana (Jurnal Pendidikan Ekonomi Undiksha, 2020)
The classroom action research is based on lack of student critical thinking skill has an impact result of learning. This study aims to analyze teacher and students’ activities, to improve students’ critical thinking skills and student response by applying Problem Based Learning model to the APBN and APBD materials in Development on eleventh grade of Social Major 3 in 1st Senior High School Puri Mojokerto. This study was conducted in two cycles. Each cycle uses the stages of study plan (planning), implementation (acting), observation (observing), and reflection (reflecting). The instruments used were a post-test to determine the ability to think critically and an observation sheet to find out the teacher's activities, the students' activities and students' responses to the application of Problem Based Learning model. The result showed that the students' critical thinking skills increased from 50% in cycle 1 to 87.5% in cycle 2. Furthermore, the teacher activity showed an increase from 74,76% in cycle 1 to 91.9% in cycle 2. While the students' activity also experienced an increase from 78.19% in cycle 1 to 84.57% in cycle 2, and the students' response reached 89.06%. Therefore, it can be concluded that based on the results, the application of Problem Based Learning model can increase students' critical thinking skills.